Results of the Application of Phototherapeutic Keratectomy in the Elderly with Bullous Keratopathy - Osbel Alfonso Sánchez; Sandra Saray Quignón Santana; Rolando Delgado Figueredo; Alain Barceló Torriente (Medisur)
Background: Many countries have conducted studies on the benefits of phototherapeutic keratectomy in corneal diseases; few references have been found in our country to address the results of the application of the excimer laser in the elderly suffering from bullous keratopathy. Objective: To assess the results of the application of phototherapeutic keratectomy in the eldrly with bullous keratopathy. Methods: A case series study was conducted in 2009, in the Cornea Department of the Dr. Gustavo Aldereguía Lima General University Hospital of Cienfuegos. It included 16 elderly with bullous keratopathy not leading to penetrating keratoplasty. After considering the ethical and biomedical assessment, phototherapeutic keratectomy was performed. Treatment was indicated and follow up was performed with an assessment of symptoms and signs until the third month. Results: In the postoperative stage symptoms decreased and the most frequent sign was the haze followed by slight increase in best corrected visual acuity. Conclusions: The application of phototherapeutic keratectomy in patients that did not apply for cornea transplant helps improving eye condition, reduces symptoms and improves visual acuity.